Idyllic pastoral: environmental scenic remedial sublimes for Apocalyptic ecophobia in Margaret Atwood's the year of the flood - Jujar Singh, Hardev Kaur; Akram Yahya, Amani; Haw Ching, Florence Toh; Bahar, Ida Baizura (Rigeo, 2021)
This paper explores idyllic pastoral as a remedy of apocalyptic eco[1]phobia in Margaret Atwood's The Year of the Flood. It looks into eco-phobia as intimidating fear felt by the characters when they undergo imminent apocalyptic experience. It unravels the contiguous affinity between eco-phobia and the environment which is blatantly projected in the novel for the sake of highlighting its negative effect on the characters who suffer from terrifying eco-phobic feelings. The study sheds light on pastoral as ideal environmental scenery providing the characters with possible outlets to escape destructive apocalyptic events caused by their feelings of eco-phobia. Pastoral, therefore, will be discussed via applying Greg Garrard's concept of pastoral that includes scenic sublimes, like solitary landscapes, wilderness, forests, lakes, mountains and cliffs that embody ideal alternatives for the threatened environmental places. Accordingly, the study attempts to demonstrate how the fictional characters' resort to these scenic sublimes to seek peace and solace of mind by living satisfactorily in their natural milieus. Such scenic sublimes will be discovered as ultimate condition leading the characters to recognize the vital function of nature to their life. Consequently, scenic sublimes make them strongly conscious of nature's crucial significance to their lives. In the long run, they become able to preserve environment for avoiding any calamitous destruction. In this respect, the concept of apocalypse will be polarized in the discussion to examine Atwood's deliberate depiction of natural catastrophes as impending apocalyptic threat. Thus, the study's gap lies in exploring pastoral as a decisive remedy for echo-phobia.